Testosterone and gonadotropin levels in men with dementia. - Hogervorst, E; Combrinck, M; Smith, A (2003)
OBJECTIVES: Sex steroids such as testosterone and estradiol might protect the brain against Alzheimer's disease (AD). We previously found lower levels of testosterone in men with AD compared with controls. We wanted to assess levels of pituitary gonadotropins that regulate sex steroid levels, to determine whether primary or secondary hypogonadism was responsible for low levels of testosterone in cases. METHOD: We included 45 men with AD (McKhann, 1987), 15 men with other types of dementia and 133 elderly controls from the Oxford Project to Investigate Memory and Ageing. Gonadotropins (follicle stimulating hormone or FSH and luteinizing hormone or LH), sex hormone binding globulin (SHBG, which determines the amount of free testosterone) and testosterone were measured using enzyme immunoassays. RESULTS: We found no difference in average LH (8.7 +/- 9 UI/L), FSH (13 +/- 17 UI/L) or SHBG (44 +/- 18 nmol/L) levels between AD cases and controls. Similar to our earlier findings, testosterone levels were significantly lower in men with AD (13 +/- 6 nmol/L) compared with controls (17 +/- 8, O.R. = 0.92, 95% C.I. = 0.87 to 0.97, p<0.005). Results were unchanged when controlled for age, SHBG and gonadotropin levels. CONCLUSION: Although normal, the levels of gonadotropins were inappropriately low for the levels of testosterone. Our results support a preliminary conclusion that secondary hypogonadism occurs in men with AD. This could be a consequence of brain degeneration. This is contrary to an earlier study (Bowen, 1999) that found raised levels of gonadotropins in cases with AD, suggesting primary hypogonadism. Our cohort was younger than theirs and gonadotropin levels increase with age. We are enlarging our data set to investigate whether primary hypogonadism occurs in older cases with AD or whether secondary hypogonadism precedes cognitive dysfunction in men at risk for AD. If this is true, testosterone replacement therapy for hypogonadal men at risk for dementia may be indicated.